Pengaruh Penambahan Garam pada Perubahan Karakteristik Kimia dan Pertumbuhan Bakteri pada Ikan Sepat Rawa (Trichogaster trichopterus): The Effect of Salt Addition on Chemical Characteristics of and Bacterial Growth on Three Spot Gourami (Trichogaster trichopterus) - Findya Puspitasari; Siti Aisyah; Siti Agustiana Wilianti; Kemas Syech Albarah; Rabiatul Adawyah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2021)
This study aimed to determine the effect of addition of different salt concentrations on chemical characteristics and bacterial growth of Three Spot Gourami (Trichogaster trichopterus). The treatments given were no addition of salt (A) as a control, 5% salt (B), 10% salt (C) and 15% salt (D). The moisture was measured using the drying method, while protein content was analysed using the Kjeldahl method. Amino acids content was determined using the high performance liquid chromatography (HPLC) method and the microbial growth was observed using the total plate count (TPC) method. The best treatment was treatment D with the addition of salt with a concentration of 15% resulting in water content of three spot gourami 61.35%, protein content 31.61%, and TPC 5.87 log10 CFU/mL. The highest profile of essential amino acids in treatment B was lysine at 2.20% and the highest non-essential amino acids in treatment B was glutamic acid at 4.34%.